Mss4 protein is a regulator of stress response and apoptosis - Walter, Beate Maria; Nordhoff, Carolin; Schneider, Stefan W. (Cell death & disease, 2012)
Mss4 (mammalian suppressor of Sec4) is an evolutionarily highly conserved protein and shows high sequence and structural similarity to nucleotide exchange factors. Although Mss4 tightly binds a series of exocytic Rab GTPases, it exercises only a low catalytic activity. Therefore Mss4 was proposed to work rather as a chaperone, protecting nucleotide free Rabs from degradation than as a nucleotide exchange factor. Here we provide further evidence for chaperone-like properties of Mss4. We show that expression levels of cellular Mss4 mRNA and protein are rapidly changed in response to a broad range of extracellular stress stimuli. The alterations are regulated mostly via the (c-jun NH2-terminal kinase) JNK stress MAPK signaling pathway and the mode of regulation resembles that of heat shock proteins. Similar to heat shock proteins, upregulation of Mss4 after stress stimulation functions protectively against the programmed cell death. Molecular analysis of the Mss4-mediated inhibition of apoptosis showed that interaction of Mss4 with eIF3f (eukaryotic translation initiation factor 3 subunit f), a member of the translation initiation complex and a protein with distinct pro-apoptotic properties, is the critical event in the anti-apoptotic action of Mss4.